An investigation of how Absa’s integration of online service chatbots has influenced customer’s perceptions with regards to customer-based brand equity. - Witchell, Chane (The IIE, 2022)
Due to the rapid rise of technology, such as artificial intelligence, there has been an increase in the need for brands to adapt in order to keep up with customer expectations and requirements. This increase is becoming more apparent, specifically within the financial sector, as more South African banks, such as Absa bank, are implementing artificial intelligent systems, specifically chatbots, within their online backing services. In addition, brands are faced with the challenge of building and developing brand equity, due to the vast array of benefits a brand could receive if achieved. Subsequently, this begs the question, how has Absa’s integration of online service chatbots influenced customer perceptions with regards to Keller’s (2001) customer-based brand equity. Thus, a qualitative study was implemented where in-depth semi-structured interviews were conducted in order to collect relevant and sufficient data regarding customer perceptions of Absa’s integration of online service chatbots, with regards to Keller’s (2001) customer-based brand equity model. Furthermore, a thematic content analysis was applied which enabled the interpretation of key findings. Conclusively, there were more favourable and positive perceptions, however due to various negative perceptions regarding specific aspects, it was concluded that Absa’s chatbots have not yet reached absolute brand equity, according to their customer perceptions.
Keywords: Digital marketing; Customer behaviour; Banking